Der sozialgeographische Einfluß des Kastenwesens auf Siedlung und Agrarstruktur im südlichen Indien.: Teil II: Agrarstruktur und Kastenwesen im südlichen Indien (Andhara Pradesh). Sozialgeographische Strukturdiagnose zu einem Entwicklungsproblem - Bronger, Dirk (ERDKUNDE, 1970)
The rapid rise in population since 1950, whose extent could hardly be visualized, removed last doubts about the necessity to favour the development of agriculture, i.e. to realize an increase in productivity. The main obstacles are based not only on an unsound agricultural structure, but also on the backwardness of the social structure, which finds its expression in the caste. The rapid rise in population since 1950, whose extent could hardly be visualized, removed last doubts about the necessity to favour the development of agriculture, i.e. to realize an increase in productivity. The main obstacles are based not only on an unsound agricultural structure, but also on the backwardness of the social structure, which finds its expression in the caste system. In this article comments on the problems of development in Indian agriculture are made with respect to these facts. The caste system is treated with a view to 1) the structure of the agrarian society; 2) land-tenure; 3) the structure of property/size of holdings; 4) land use; 5) the economic attitude of the agricultural population. The results should help to rejudge the caste system with a view to urgent improvements in the agricultural situation with special regard to its structures and a rise in productivity. 1) The most important feature of the social structure - and of the ensuing influences on productivity - is the fact that social levels have their origin mainly in the caste system. The landlords are generally members of the two highest varnas, the Brahmins and the Kshatriyas, who do not cultivate their land themselves, but draw only money from it. Apart from Muslims there also landlords among the peasant-caste Reddies, who rank first in the Sudra hierarchy. The ryots, i.e. peasants cultivating their own land, are from the upper Sudra castes of Reddies, Kapus, Vellala, Lingayats and others. The tenants range from the upper to the lower Sudra castes, whereas the agricultural labourers come from the lowest Sudra castes, and expecially Parias. 2) Even more important is the fact that the land tenure is divided according to castes. While generally the largest part of the land belongs to only a small number of upper caste families, the large mass of the rural population from the lower Sudra castes and Parias are mostly without land property; and only in a very limited number of cases can the amount of land guarantee sufficient food. Their share in valuable irrigated fields is even more unsatisfactory. 3) In addition the property of the few upper-caste families is much better organized, forming larger blocks whereas the small fields of the lower Sudras and Parias are widely distributed over the whole area. Due to the rapid increase in fragmentation in connection with population growth the organizational structure has grown ever worse. The task of distributing the fields of upper castes is much easier, because the large size of a number of similar fields favours an arrangement among the inheritors, so that the respective fields are not subdivided. In a case of inheritance among the lower castes the property must be carefully subdivided, since everyone wants his share in the many different qualities of the dry and irrigated farming area. It is therefore necessary to divide an individual field among all the in heritors. The consequence is a rapid decrease of average field sizes of the small land owners, i.e. members of the lower Sudra castes and Parias. 4) The problem of the connection between the caste system and land use was investigated on the basis of two village surveys. It was observed that cash crops (ground nuts, castor, rice, maize and tobacco) are mainly grown by the upper castes, whereas the members of lower castes are forced to grow only foodcrops i.e. rice, millets and pulses. 5) Since caste rules forbid any fieldwork by Brahmins and Kshatriyas, their fields are worked by tenants without any rights of usage and by labourers. The labourers are by no means interested in careful cultivation which results in the fact that the units with the best structure and with the most favourable financial background for improvement and a rise in productivity are not seldom in the worst state. In addition, there is often no reason for the landlord especially the absentee’Mandlord, to cultivate the dry fields, since they are independent of the risky yields and tend to leave part of their land fallow (social fallow). On the other hand the lower-Sudra land owners cannot achieve a reasonable improvement on their small plots or share of plots, because of their dispersion and lack of finances. The necessary care in cultivating those small and medium-sized units is often missing, because the respective owners are also busy as potters, weavers, washermen and so on according to their caste. The conclusion is that the caste system, through its barriers for the individual, not only prevents an efective cultivation of rural economic units, but also the reasonable use of human labour, because the labour force of both upper and lower castes is extremely reduced by religious bonds to one profession. The caste system is therefore an important, if not the most important obstacle on the way to a more productive agriculture.